Reinventing Tradition: Hybrid Governance and the Transformation of Adat Institutions in Langsa Villages through an Islamic Political Perspective (State Islamic Institute of Kudus (IAIN Kudus), 2025)
This article examines the transformation of traditional institutions in Aceh within the context of the post-conflict revival of adat-based village governance and the implementation of special autonomy. The main focus is to understand how traditional institutions are incorporated into modern governance systems, and to what extent they are able to maintain their symbolic authority and capacity for social mobilization amid the expansion of village bureaucracy. This research employs a qualitative method, conducted in two villages in Langsa City, namely Gampong Kuala Langsa and Gampong Meurandeh Dayah. The findings show that adat norms and bureaucratic logic coexist in village governance, but their relationship is not always harmonious. While village officials work within the framework of state regulations, adat institutions continue to play a vital role in social life, including conflict resolution, religious activities, and collective rituals. This demonstrates that adat institutions persist not only as symbolic traditions but also as active actors in shaping hybrid forms of local governance. These findings reaffirm the importance of understanding the state as a socially constructed entity, embedded in practices and symbols that remain vibrant at the local level.